2021
DOI: 10.1021/acsami.1c11753
|View full text |Cite
|
Sign up to set email alerts
|

Near-Unity-Efficiency Energy Transfer from Perovskite to Monolayer Semiconductor through Long-Range Migration and Asymmetric Interfacial Transfer

Abstract: van der Waals heterostructures combining perovskites of strong light absorption with atomically thin two-dimensional (2D) transition-metal dichalcogenides (TMDs) hold great potential for light-harvesting and optoelectronic applications. However, current research studies integrating TMDs with low-dimensional perovskite nanomaterials generally suffer from poor carrier/energy transport and harnessing, stemming from poor interfacial interaction due to the nanostructured nature and ligands on surface/interface. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Several low-dimensional light-harvesting materials such as colloidal quantum dots, perovskites, nanowires, and other layered materials have been integrated with TMDCs. [14][15][16][17][18][19] Among them, cesium lead bromide (CsPbBr 3 ) nanocrystals represent an emerging class of materials with excellent visible light absorption, high defect tolerance, long carrier diffusion length, and size-dependent electronic properties, showing an E g of ≈2.4 eV. [16] In fact, in initial works, the interaction between CsPbBr 3 and Se-based TMDCs was studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several low-dimensional light-harvesting materials such as colloidal quantum dots, perovskites, nanowires, and other layered materials have been integrated with TMDCs. [14][15][16][17][18][19] Among them, cesium lead bromide (CsPbBr 3 ) nanocrystals represent an emerging class of materials with excellent visible light absorption, high defect tolerance, long carrier diffusion length, and size-dependent electronic properties, showing an E g of ≈2.4 eV. [16] In fact, in initial works, the interaction between CsPbBr 3 and Se-based TMDCs was studied.…”
Section: Introductionmentioning
confidence: 99%
“…[16] In fact, in initial works, the interaction between CsPbBr 3 and Se-based TMDCs was studied. For example, Zhang et al [14] demonstrated near-unity energy transfer efficiency between bulk CsPbBr 3 and WSe 2 and Hassan et al [20] reported an enhanced photocurrent in a CsPbBr 3 nanocrystals and MoSe 2 nanosheets hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the triplet in HSs decays slower with increasing L and approaches that of pure PdOEP with an L of 40 nm, confirming the determining role of triplet diffusion on the triplet energy/charge transfer kinetics. Here, we employ a one-dimensional diffusion model to describe the diffusion-controlled triplet transfer behavior in such organic/2D bilayer HSs. ,, In this diffusion model, the triplet population x nm away from the interface at delay time t can be described by the following equation: where D is the triplet diffusion coefficient in PdOEP film and τ 0 is the triplet lifetime of a pure PdOEP film without a TMD quenching layer (∼190 ns). Assuming that the overall transfer process is limited by the triplet diffusion step and solving eq with boundary conditions, we obtain the approximate relationship between the triplet lifetime τ HS in HSs and the PdOEP thickness L …”
Section: Resultsmentioning
confidence: 99%
“…Atomically thin two-dimensional (2D) layered semiconductors such as transition metal dichalcogenides (TMDs) possess extraordinary electronic and optical properties that are promising for next-generation optoelectronic applications such as photovoltaics, photodetectors, field effect transistors, and so on. In particular, the atomic thinness and smoothness of 2D layered materials without surface dangling bonds enable the facile construction of van der Waals heterostructures (HSs) with well-defined interfaces and rich functionalities. So far, a large family of functional components have been integrated as building blocks with 2D layered semiconductors to engineer their light–matter interaction and photophysical properties, such as quantum dots, organic molecules, and layered and bulk semiconductors. , Among them, organic molecules are well-known for their strong and tunable absorption but poor carrier mobility, which complements very well the monolayer semiconductors with excellent carrier transport but low light absorption. Organic/inorganic hybrid HSs by interfacing monolayer semiconductors with organic counterparts, combining the distinct advantages of both components, have led to optoelectronic devices with enhanced performance. ,,,, …”
mentioning
confidence: 99%
See 1 more Smart Citation